2022
DOI: 10.1186/s12909-022-03317-7
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual reality in lumbar puncture training improves students learning experience

Abstract: Background Lumbar puncture (LP) is a commonly performed medical procedure in a wide range of indications. Virtual reality (VR) provides a stimulating, safe and efficient learning environment. We report the design and the evaluation of a three dimensions (3D) video for LP training. Methods We recorded a stereoscopic 180-degrees 3D video from two LPs performed in clinical settings in Fernand Widal Lariboisière University Hospital, Paris, France. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Farra et al ( 62 ) and Vrillon et al ( 63 ) emphasized that students were highly satisfied with VR-based education in their studies ( 62 , 63 ). Chang ( 64 ) stated that education conducted using VR provided students with an enjoyable learning experience, and students were satisfied with this method ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Farra et al ( 62 ) and Vrillon et al ( 63 ) emphasized that students were highly satisfied with VR-based education in their studies ( 62 , 63 ). Chang ( 64 ) stated that education conducted using VR provided students with an enjoyable learning experience, and students were satisfied with this method ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of VR in training is currently occurring mainly in the healthcare field [18,19]. In this aspect, its usefulness is emphasised when making diagnostic or therapeutic decisions in health interventions, in the broadest sense of the term [20].…”
Section: Introductionmentioning
confidence: 99%
“…The subjects can concentrate, immerse themselves in VR, and temporarily detach from the real world by shifting their attention. As a distraction technique, it can effectively reduce the fear of children in the interventional procedure, including lumbar puncture [ 11 , 12 ]. Studies have shown that VR has been used as an additional tool for treating acute and chronic pain and can effectively reduce the pain caused by injections and dressing changes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%